Numerical Calculation of Three-Dimensional Ground State Potential Energy Function of Na2F System - Yue Wang; Yu Liu; BiLv Fang; Gan Gao; Chengwen Zhang; Dezhi Dong (Advances in Mathematical Physics)
We present a new three-dimensional global potential energy surface (PES) for the ground state of Na2F system. A total of about 1460 points were generated for the PES. All of the points have been carried out by using the coupled-cluster single-, double-, and perturbative triple-excitations [CCSD(T)]. Two Jacobi coordinates, R and θ, and the frozen molecular equilibrium geometries were used. We mixed the basis sets of aug-cc-pCVQZ for the sodium atom and the basis sets of aug-cc-pCVDZ for the fluorine atom with an additional (3s3p2d) set of midbond functions; the energies obtained were extrapolated to the complete basis set limit. The whole calculation adopted supramolecular approximation approach. We divided the potential energy surface into three regions, the peak region, the well region, and the long range region, and calculate the single point energy, respectively. Our ab initio calculations will be useful for future studies of the collision-induced absorption for the Na2-F dimer, and it can be used for modeling the dynamical behavior in Na2F system too.